Islam, Muslims and the mosque institution: ideology institutional harmony in Islamic society - Omer, Spahic (s.n, 2012)
This research will explore the close relationship between Islam, Muslims and the mosque institution in the development of Islamic society, both in theory and practice. On this relationship depends the creation and sustaining of what could be classified as ideological institutions harmony, which is a key to the civilization decline of Islamic society.